Cognitive Impairment In Patients With Alcohol Abuse - Severyn, Iuliia; Hrytsenko, Ilona (Psychiatry, Neurology and Medical Psychology, 2017)
The article deals with the peculiarities of the diagnosis of cognitive disorders caused by brain dysfunction in patients with alcohol abuse through neuropsychological testing. The results showed that the brain deficiency in patients at the early stages of alcohol intoxication, manifested in violation of higher mental functions, verified through a wide range of highly sensitive neuropsychological tests along with clinic-neurological examination. Identified cognitive impairment were diffuse and manifest violations of dynamic movements, spatial and visual gnosis, oralaural and visual memory, indicating the dysfunction of all the brain divisions. Using the neuropsychological tests has allowed not only to diagnose cognitive impairment and to identify degree of their violations, but also to determine the localization of pathological changes in the brain.